(untitled) (Harmoni, 2014)
Duties and functions of the Office of Religious Affairs ( KUA ) in general are reconciliation and marriage records services, mosques coaching, zakat, Wakaf, Baitul Mal, social worship, and the development of sakinah family as well as the Hajj guidance. But the main activities carried out by the Office of Religious Affairs is a marriage, wakaf and hajj guidance services. Since the beginning of September 2013, the head of (KUA) in City of Kediri detained by the State Attorney for alleged graft. In term of marriage, giving tradition as a thank you to the KUA officers has been in going since so long. Its becames a serious problem in the community, especially after the communication forum of the head of KUA in East Java Province (FKK - KUA) refused to serve outside the KUA office. This study describes the successful of KUA services in Kediri after declaration of FKK-KUA. The study also recommends a legal framework that govern the marriage records system.